Formula Optimization and Antioxidant Activity of High-added Tartary Buckwheat Noodles - Weifeng KONG; Xiuhua LI; Lijun SHAO; Yiting JIANG; Feilong JU; Jin LIANG; Yue SUN; Hong CHEN; Xueling LI (Shipin gongye ke-ji, 2022)
To optimize the formula of high addition tartary buckwheat noodles and study its antioxidant activity, single factor experiments and response surface method were used to determine the optimal formula of high-added tartary buckwheat noodles. Secondly, the thermal mechanical properties of dough and the cooking characteristics of noodle and its antioxidant activity were determined. The results showed that the best formula of high addition tartary buckwheat noodles were as follows: 62% tartary buckwheat, 38% flour, 0.4% sucrose ester, 0.2% edible alkali, 0.4% konjac gum and 2% salt. The dough cooking stability (C4/C3) of this formula was better than that of the pure wheat noodles and the comprehensive score of the high addition tartary buckwheat noodles prepared with this formula was the highest. The total phenol content and in vitro antioxidant activity results showed that the total phenol content and antioxidant capacity of the improved group were significantly higher than the pure wheat noodles (P<0.05), and the total phenolic content of the improved group was 9.11 mg GAE/g, the scavenging rate of DPPH· and ABTS+· was respectively 70.55% and 87.73%. While the total phenolic content, the scavenging rate of DPPH· and ABTS+· were 1.11 mg GAE/g, 36.70% and 9.10%, respectively. According to the results of cooking characteristics, the cooking loss rate, break rate and noodle soup turbidity of Tartary buckwheat noodles without improved agents were significantly greater than that of pure wheat noodles (P<0.05), while the cooking loss rate and break rate of the improved group were not significantly different from pure wheat noodles, but the turbidity of the improved noodle soup was significant. Therefore, the optimized high content tartary buckwheat flour mixture had the higher antioxidant activity and the noodle processing suitability.